Physics English-Maithili - (:unkn) unknown (My University, 2019)
The vision is to create a knowledge society by transcending language barriers. NTM aims to disseminate knowledge in all Indian languages listed in the VIII Schedule of the Indian Constitution through translation. All textual materials meant for All textual materials meant for the dissemination of knowledge constitute the corpus of KT for NTM.
Translation Equivalents in Indian Languages: Physics- English - Maithili
Keywords: English; Maithili